Analisa Visualisasi Data Kematian Yang Disebabkan Oleh Penyakit Hiv Dan Malaria Diseluruh Dunia Dengan Metode Business Intelligence Menggunakan Dashboard Tableau - Mutiara Zahra Arifin; Bagas Kembar Rezkyllah; Fadli Hardiyanto Putra; Rizky Ramdhani; Firman Noor Hasan (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2022)
HIV and Malaria are diseases that claim many victims in all parts of the world. Although in some countries there are treatments that can reduce mortality rates, not all countries have these treatments. So there are still many deaths from these two diseases. This study will analyze data visualization from kaggle in the form of dashboards and visualizations using the story feature available on Tableau, with the aim of this research being able to find out how many people die due to HIV and Malaria worldwide. Of all that, a method called Business Intelligence uses an interactive dashboard option provided by Tableau to be used as a decision making tool, which can then be converted into a visualization which will later be combined into an information dashboard. This study obtained the results of the BI dashboard display starting from the number of HIV and Malaria death cases worldwide, the distribution of death cases worldwide and countries with the highest number of death cases. This research yielded accurate results, namely the number of deaths from HIV was 36,364,419 people and the number of deaths from malaria was 25,342,676 people, the country with the most HIV deaths came from South Africa and the country with the most Malaria deaths came from Nigeria, and a comparison of the results of HIV deaths and Malaria in Indonesia.